LipidQuant 1.0: automated data processing in lipid class separation–mass spectrometry quantitative workflows - Wolrab, Denise; Cífková, Eva; Čáň, Pavel; Lísa, Miroslav; Peterka, Ondřej; Chocholoušková, Michaela; Jirásko, Robert; Holčapek, Michal (My University, 2021)
We present the LipidQuant 1.0 tool for automated data processing workflows in lipidomic quantitation based on lipid class separation coupled with high-resolution mass spectrometry. Lipid class separation workflows, such as hydrophilic interaction liquid chromatography or supercritical fluid chromatography, should be preferred in lipidomic quantitation due to the coionization of lipid class internal standards with analytes from the same class. The individual steps in the LipidQuant workflow are explained, including lipid identification, quantitation, isotopic correc- tion and reporting results. We show the application of LipidQuant data processing to a small cohort of human serum samples.
LipidQuant 1.0: automatizované zpracování dat při oddělování lipidových tříd – kvantitativní pracovní postupy hmotnostní spektrometrie
Keywords: LipidQuant; lipids; mass spectrometry; quantification; lipidomics; LipidQuant; lipidy; hmotnostní spektrometrie; kvantifikace; lipidomika